Mobile Phone Based Remote Control System For Furnace Automation (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Nowadays, an increasing role in various technologies holds electronic devices that automate the various systems to facilitate people's daily life. This publication describes one of those types of automation capabilities, as a control system using mobile phones and mobile communications. Innovative approaches for the modification can be used for various purposes, such as a room or vehicle security alarm systems, remote management for various processes, the heating system furnace firing, the combustion process control, as well as many other remote management and control purposes.